2019
DOI: 10.1016/j.apm.2019.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in fluid-conveying NSGT nanotubes with geometric imperfections

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Chaos in fluid-conveying nanotubes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…They concluded that the stiffness-hardening effect is underestimated in NSGT without the thickness effect, and the stiffnesshardening and stiffness-softening effects of NSGT with the thickness effect can be not only length-dependent but also thickness-dependent. Through a nonlinear analysis, the effect of a geometric imperfection on the chaotic response of fluid-conveying nanotubes was studied by Ghayesh et al [29]. They modeled the nanotubes based on NSGT, incorporated the effects of relative motion between the nanofluid and nanotube using Karniadakis-Beskok assumptions and studied the effect of geometric imperfection on the motion response.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the stiffness-hardening effect is underestimated in NSGT without the thickness effect, and the stiffnesshardening and stiffness-softening effects of NSGT with the thickness effect can be not only length-dependent but also thickness-dependent. Through a nonlinear analysis, the effect of a geometric imperfection on the chaotic response of fluid-conveying nanotubes was studied by Ghayesh et al [29]. They modeled the nanotubes based on NSGT, incorporated the effects of relative motion between the nanofluid and nanotube using Karniadakis-Beskok assumptions and studied the effect of geometric imperfection on the motion response.…”
Section: Introductionmentioning
confidence: 99%